Association of social capital with self-perceived eHealth literacy among community-dwelling older people: Age and gender differences - Cao, Chenglin; Cao, Wenwen; Zheng, Xin; Ji, Kai; Wu, Yunwei; Hu, Zhi; Chen, Ruoling; Bai, Zhongliang (Frontiers in Public Health, 2023)
Background: Studies have confirmed that social factors, including social capital and eHealth literacy, are important in later life. Currently, limited studies are available on the relationship between social capital and eHealth literacy, and whether such a relationship exists among older people from different age groups and genders remains unclear. Consequently, this study aimed to investigate the association between social capital and eHealth literacy, specifically by comparing age and gender variations. Methods: In a cross-sectional study, 4257 residents aged ≥ 60 years and dwelling in the community were randomly selected from four cities in China. A structured questionnaire was employed to collect data on general characteristics, socioeconomic status, social capital, and eHealth literacy. Generalized linear models were used to assess these associations. Results: Finally, data analysis included 4218 respondents (71.91±7.15 years). Overall, social participation, social connection, trust, cohesion, and reciprocity were all statistically linked to eHealth literacy (P<0.05), while such an association was not identified for social support (P>0.05). Specifically, a higher level of social participation was associated with better eHealth literacy scores among participants aged 70–79 years (P<0.001), and a higher level of social connection was associated with better eHealth literacy scores for those aged 60–69 and 70–79 years (P<0.001). Meanwhile, no gender differences were identified. Conclusions: An association between social capital and eHealth literacy, particularly age differences, was found. Our findings provide a reference for developing targeted measures to improve self-perceived eHealth literacy among older people, which is essential for achieving active and healthy aging and developing our knowledge and understanding of relevant theories, concepts, and evidence within the field of health and social capital.